167k views
4 votes
Use the definition of Taylor series to find the Taylor series, centered at c, for the function. f(x) = sin x, c = 3π/4

User Genonymous
by
4.7k points

1 Answer

4 votes

Answer:


\sin(x) = \sum\limit^(\infty)_(n = 0) (1)/(\sqrt 2)((-1)^(n(n+1)/2))/(n!)(x - (3\pi)/(4))^n

Explanation:

Given


f(x) = \sin x\\


c = (3\pi)/(4)

Required

Find the Taylor series

The Taylor series of a function is defines as:


f(x) = f(c) + f'(c)(x -c) + (f

We have:


c = (3\pi)/(4)


f(x) = \sin x\\


f(c) = \sin(c)


f(c) = \sin((3\pi)/(4))

This gives:


f(c) = (1)/(\sqrt 2)

We have:


f(c) = \sin((3\pi)/(4))

Differentiate


f'(c) = \cos((3\pi)/(4))

This gives:


f'(c) = -(1)/(\sqrt 2)

We have:


f'(c) = \cos((3\pi)/(4))

Differentiate


f

This gives:


f

We have:


f

Differentiate


f

This gives:


f


f

So, we have:


f(c) = (1)/(\sqrt 2)


f'(c) = -(1)/(\sqrt 2)


f


f


f(x) = f(c) + f'(c)(x -c) + (f

becomes


f(x) = (1)/(\sqrt 2) - (1)/(\sqrt 2)(x - (3\pi)/(4)) -(1/\sqrt 2)/(2!)(x - (3\pi)/(4))^2 +(1/\sqrt 2)/(3!)(x - (3\pi)/(4))^3 + ... +(f^n(c))/(n!)(x - (3\pi)/(4))^n

Rewrite as:


f(x) = (1)/(\sqrt 2) + ((-1))/(\sqrt 2)(x - (3\pi)/(4)) +((-1)/\sqrt 2)/(2!)(x - (3\pi)/(4))^2 +((-1)^2/\sqrt 2)/(3!)(x - (3\pi)/(4))^3 + ... +(f^n(c))/(n!)(x - (3\pi)/(4))^n

Generally, the expression becomes


f(x) = \sum\limit^(\infty)_(n = 0) (1)/(\sqrt 2)((-1)^(n(n+1)/2))/(n!)(x - (3\pi)/(4))^n

Hence:


\sin(x) = \sum\limit^(\infty)_(n = 0) (1)/(\sqrt 2)((-1)^(n(n+1)/2))/(n!)(x - (3\pi)/(4))^n

User Ryan From Denver
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.